A Meta-Analysis of Mobile Phone Use and Presence - Courtright, John; CAPLAN, SCOTT (Human Communication & Technology, 2020)
This research reports the results of two meta-analyses on 43 empirical studies that have investigated the effects of the presence and use of mobile phones during interpersonal interactions.  Six of these investigations focused on the “mere presence effect,” which asserts that the presence (but not use) of a mobile phone leads to more negative perceptions of one’s interactional partner.  The meta-analysis did not provide support for this effect.  Thirty-seven studies focused on the effects of “phone snubbing” (“phubbing”) which addresses the use of a mobile phone during interactions.  This second meta-analysis found a relatively robust effect which clearly leads to more negative perceptions by the non-using partner.  Although numerous potential moderators were examined, none of theoretical interest were found to moderate these effects.